Transforming education with innovative e-learning tools in blended learning / Nurulashikin Romli ... [et al.] - Romli, Nurulashikin; Mohamed, Suhana; Ismail, Azianti; Haris, Sharazad; Md Isa, Mohamad Azwan (Universiti Teknologi MARA, Kedah, 2023)
Blended learning has revolutionized education by combining traditional classroom and online learning, creating flexible and accessible learning environments. It aims to provide a customized and efficient learning experience, preparing students for the digital era. Integrating e-learning tools enhances education quality and promotes engagement, motivation and lifelong learning. Blended learning and integrating e-learning tools have positively impacted student flexibility, accessibility, global learning, and equal learning opportunities in the Regulatory Framework in the Capital Market (INV537). The interactive tools have increased student enthusiasm and deepened understanding, while the flexibility of blended learning has accommodated diverse needs.